Chapter La città come contesto e soggetto educativo nel ventunesimo secolo. Pedagogia delle aree urbane: da spazi di crisi a luoghi della relazione - Proli, Maria Grazia (Studies on Adult Learning and Education, 2022)
The paper resumes the outcomes of the literature review conducted from the general theme regarding the city as an educational context and subject in the twenty-first century and presents a summary of the research design undertaken. The aim is to investigate the city as a 'learning city' where educational and training processes can become engines of regeneration. It is also intended to survey some examples of generative transformations traceable to the development trajectories drawn by Agenda 2030 that emerge in the learning city model, in order to understand their impact on the communities involved, the policies and the professional figures required to govern the processes.